Потери эксергетической мощности в теплоутилизационных системах с пластинчатыми теплоутилизаторами - Фиалко, Н. М.; Степанова, А. И.; Навродская, Р. А. (Енергетика і автоматика, 2017)
LOSS OF EXERGENCY CAPACITY IN HEAT UTILIZATION SYSTEMS WITH PLATE INSULATED HEAT UTILIZERS N. Fialko, А. Stepanovа, R. Navrodska Abstract. The problem of developing efficient technologies for utilizing the heat of waste gases from power plants is an important part of the overall problem of modernizing Ukraine’s energy sector. Development of high-quality heat recovery equipment for power plants of various types is inextricably linked with the development and use of effective methods for optimizing heat recovery systems. These methods are quite diverse and can be based on complex approaches that include exergy methods combined with methods of thermodynamics of irreversible processes. This determines the relevance of the work. The purpose of the work is to increase the efficiency of the plate heat exchangers by reducing the losses of exergy power. The work analyses the loss of exergy power in heat conduction processes during the transfer of heat through the cross-section of an unlimited plate. An unlimited plate simulated the gas-air plate heat exchanger plate. The results of numerical calculations of losses of exergic power in heat conduction processes in an unbounded plate under boundary conditions of the third kind are presented. The mathematical model of the studied processes includes the exergy equation, the balance equation of exergy and entropy, the equation of continuity of a three-phase thermodynamic system with a change in the concentration of one of the phases, the equation of phase motion, the energy equation, the balance equation for enthalpies, the Gibbs equation, and the heat equation for boundary conditions of the third kind. When obtaining formulas for calculating the losses of exergy power, a local differential equation of the exergy balance of a three-phase system with a variable concentration of one of the phases is used. The derivation of this equation is presented in [1]. In the equation, one of the terms determines the loss of exergy power in the system, these loss are caused by the irreversibility of the processes and are related to the thermal conductivity, phase viscosity, phase-to-phase heat exchange, and friction between phases. Based on this equation and the solution of the heat equation under boundary conditions of the third kind for an unbounded plate, formulas are obtained for calculating the loss of exergy power and the losses in the gas-air plate heat exchanger are calculated. Key words: heat recovery system, heat conduction processes, loss of exergy power